Coronary sinus-based percutaneous annuloplasty as treatment for functional mitral regurgitation: the TITAN II trial - Lipiecki, Janusz (Open Heart, 2016)
OBJECTIVE: Functional (or secondary) mitral regurgitation (FMR) is associated with greater morbidity and worse outcomes in patients with congestive heart failure (CHF) and cardiomyopathy. The Carillon® Mitral Contour System® is a coronary sinus-based percutaneous therapy to reduce FMR. We evaluated the safety and efficacy of a modified version of the Carillon device in the treatment of patients with cardiomyopathy and FMR. METHODS: 36 patients with CHF, depressed left ventricular function (ejection fraction <40%) and at least moderate FMR underwent the Carillon device implant. RESULTS: There was 1 major adverse event within 30 days—a death (not device related)—occurring 17 days after the implant. Reductions in FMR and improvements in functional class and 6 min walk tests were seen, similar to prior studies. Device fractures in the high strain region of the proximal anchor (seen in prior studies) were not seen in this study. CONCLUSIONS: The modified Carillon device was associated with improvements in clinical and echocardiographic parameters in treating patients with FMR, while successfully addressing the issue of anchor fracture. This version of the Carillon device will be used in a blinded randomised trial of symptomatic patients with FMR.